1995
DOI: 10.1159/000126901
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated 24-Hour Patterns of Somatotropin and Prolactin in Fatal Familial Insomnia

Abstract: To assess the changes in the 24-hour profiles of serum somatotropin and prolactin levels during total disruption of the sleep/wake cycle sustained over several months, we studied 2 subjects affected by fatal familial insomnia, a rare disease characterized by selective thalamic degeneration that causes chronic sleep loss. Under standardized conditions and polysomnographic control, the patients underwent repeated 24-hour study sessions covering the entire clinical course of the disease. Hormones were assayed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…It should be noted that our results obtained in healthy subjects do not fit with the current view that insomnia lowers GH secretion (Lieb et al. , 1999; Portaluppi et al. , 1995; Vgontzas et al.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that our results obtained in healthy subjects do not fit with the current view that insomnia lowers GH secretion (Lieb et al. , 1999; Portaluppi et al. , 1995; Vgontzas et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Hormonal studies in our patient demonstrated a flattening of circadian rhythmicity, which has also been described in cases of FFI (Portaluppi et al . 1995).…”
Section: Discussionsupporting
confidence: 87%
“…-Sleep disorders [delayed sleep phase syndrome (Skene et al, 1999), non-24 h sleep/ wake disorder and sleep/wake schedule disorder (Dagan & Abadi, 2001;Uchiyama & Lockley, 2015), recurrent hypersomnia (Billiard et al, 2011), SW sleep disorder (Schwartz & Roth, 2006)] -SW intolerance (Andlauer & Reinberg, 1979;Reinberg et al, 1983Reinberg et al, , 1988) -Delirium (Fitzgerald et al, 2013) -Peptic ulcer disease (Moore & Merki, 1997;Moore & Smolensky, 1991) -Affective disorders [depression (BicakovaRocher et al, 1996;Rosenwasser & WirtzJustice, 1997;Salgado-Delgado et al, 2011), mania (Klemfuss & Kripke, 1989), bipolar disorder (Abreu & Bragança, 2015)] -Parkinson's disease (Bordet et al, 2003;Fertl et al, 1991;Willison et al, 2013) -Autism spectrum disorder (Botbol et al, 2013;Tordjman et al, 2015) -Smith-Magenis syndrome (Chen et al, 2015) -Fatal familial insomnia [autosomal dominant prion brain disease (Montagna et al, 1995;Portaluppi et al, 1994aPortaluppi et al, , 1994bPortaluppi et al, , 1995] -Kidney failure, especially end-stage disease (Biasioli et al, 1988;Farfel et al, 1978;Hillier et al, 1980;Koch et al, 2009;Mojón et al, 2013;Portaluppi et al, 1990;Raff & Trivedi, 2012;Russcher et al, 2015;Wheatley et al, 1989) -Pulm...…”
Section: Discussionmentioning
confidence: 99%